2015
DOI: 10.5737/236880762513742
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and cancer: A cross-sectional study on the barriers and facilitators to exercise during cancer treatment

Abstract: • Two-thirds of the individuals decreased their exercise level during treatment. • The prevalence barriers to exercise during treatment were fatigue and lack of knowledge about benefits of exercise and existing programs. • Cancer patients would benefit from thorough and consistent education about exercise during cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
61
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 17 publications
5
61
1
1
Order By: Relevance
“…[17,[19][20][21] Results have found both individual factors and educational factors to limit participation. [17] Individual factors include physical symptoms and fatigue, whereas educational factors relate to a lack of general knowledge on the need to stay physically active during and after treatment, proper exercise prescriptions, and available exercise programs. [17] One of the most startling findings is that there is a lack of education being provided to patients on the benefits of exercise during and after BC treatment.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[17,[19][20][21] Results have found both individual factors and educational factors to limit participation. [17] Individual factors include physical symptoms and fatigue, whereas educational factors relate to a lack of general knowledge on the need to stay physically active during and after treatment, proper exercise prescriptions, and available exercise programs. [17] One of the most startling findings is that there is a lack of education being provided to patients on the benefits of exercise during and after BC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Moderate intensity exercise of various forms has been shown to mitigate many of these side effects, [5][6][7][8][9][10][11][12][13][14][15][16] however, it has been found that less than 30% of the population takes part in the recommended level of exercise. [17,18] Barriers to exercise participation for women with BC have been studied thoroughly in the literature. [17,[19][20][21] Results have found both individual factors and educational factors to limit participation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations